2014
DOI: 10.1074/jbc.m113.536045
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Enzyme Kinetic Stability by Increasing Rigidity within the Active Site

Abstract: Background: Improving the kinetic stability of enzymes is a key issue for protein engineers. Results: Mutagenesis of residues with a high B factor located within 10 Å of the catalytic Ser 105 residue enhances kinetic stability dramatically. Conclusion: Increasing the rigidity of the flexible segment within the active site improves enzymatic kinetic stability. Significance: Optimization of the active site may an alternative, efficient approach for enhancing protein stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
169
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(182 citation statements)
references
References 44 publications
7
169
0
2
Order By: Relevance
“…One of the mutants mCALB168 with three additional hydrogen bonds displayed on yeast showed 14-fold improvement in t 1/2 -value at 60°C compared to the wild type and also had higher thermo stability than a commercially available lipase (Peng 2013). Xie et al (2014) reported the use of iterative saturation mutagenesis on the structurally flexible residues of the active site of lipase B from C. antartica to improve the thermal and active site stability. One of the mutants (D223G/L278M) exhibited a 13-fold increase t 1/2 at 48°C compared to the native enzyme (Xie et al 2014).…”
Section: Development Of Thermostable Lipasesmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the mutants mCALB168 with three additional hydrogen bonds displayed on yeast showed 14-fold improvement in t 1/2 -value at 60°C compared to the wild type and also had higher thermo stability than a commercially available lipase (Peng 2013). Xie et al (2014) reported the use of iterative saturation mutagenesis on the structurally flexible residues of the active site of lipase B from C. antartica to improve the thermal and active site stability. One of the mutants (D223G/L278M) exhibited a 13-fold increase t 1/2 at 48°C compared to the native enzyme (Xie et al 2014).…”
Section: Development Of Thermostable Lipasesmentioning
confidence: 98%
“…However, at a higher temperature thermal denaturation of lipase usually takes place. Directed evolution and rational design have been used to create a permanent solution to this problem (Hwang et al 2014;Korman et al 2013;Peng 2013;Xie et al 2014;Yu et al 2012a). Rational design increased the thermostability of lipase from Rhizopus chinensis by incorporating a disulphide bond in the hinge region of the lipase lid domain based on the prediction of ''Disulfide by Design'' algorithm and 3D structural model (Hwang and Kim 2004;Yu et al 2012a).…”
Section: Development Of Thermostable Lipasesmentioning
confidence: 99%
“…This enhancement in low-temperature activity will then be accompanied by an increase in enzyme thermostability if the structural elements (e.g., Asn136 in S41) contribute to enzymatic activity by stabilizing key components that are involved in the catalytic cycle (e.g., the catalytic triad). Recently, lipase variants with an increase in both thermostability and activity have been engineered by rigidifying the catalytic residues (59,60). In this context, stabilizing the geometry of catalytic residues is a valuable strategy to engineer enzymes that couple high thermostability with high activity.…”
Section: Discussionmentioning
confidence: 99%
“…In case of conjugated AuNPs-NH 2 -lipase, nanoparticles act as a support that either minimize the denaturation process or act as a scaffold to speed up the renaturation of protein. 46 Along with the maintenance of active open conformation as mentioned earlier, immobilization generally increases the rigidity of the protein and thus increases the thermal stability of the immobilized enzyme.…”
Section: Enzyme Kinetics Measurementmentioning
confidence: 99%